2013
DOI: 10.1111/jgh.12056
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection of large gastrointestinal stromal tumors in the esophagus and stomach

Abstract: ESD appears to be an effective, safe, and feasible treatment for large-size GISTs in the esophagus and stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 48 publications
0
42
0
Order By: Relevance
“…The mean time required for these procedures has been reported to be 71 minutes (range 40-105 minutes). 145 A higher risk of perforation occurs in nonmobile fixed lesions and in lesions in which the underlying muscularis layer could not be identified on EUS. 146,147 Although ESD may provide complete resection of SELs, there are limitations to this technique.…”
Section: Esdmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean time required for these procedures has been reported to be 71 minutes (range 40-105 minutes). 145 A higher risk of perforation occurs in nonmobile fixed lesions and in lesions in which the underlying muscularis layer could not be identified on EUS. 146,147 Although ESD may provide complete resection of SELs, there are limitations to this technique.…”
Section: Esdmentioning
confidence: 99%
“…ESD is technically challenging, time consuming, and has limited application for large tumors (>5 cm) because of a reported perforation rate of up to 19% for larger lesions. 145 Additional risks include positive resection margins, bleeding, and tumor spillage because of a disrupted lesion capsule. Therefore, despite studies reporting low recurrence rates with ESD of SELs up to 5 cm, its widespread application for this indication remains controversial.…”
Section: Esdmentioning
confidence: 99%
“…Moreover, a tumor located in the esophagus or near the esophagus-gastric junction may be challenging to perform with laparoscopic surgery. 20 Despite the rapid development of endoscopic technology in recent years, surgery is still preferred for the removal of SETs >2 cm, while ET is favored for removing SETs <2 cm. 21 Many studies have reported the efficacy and safety of ET in treating gastric SETs.…”
Section: B)mentioning
confidence: 99%
“…One study conducted by Zhang S. et al [12] reported that the complete resection rate of ESD was 94.4 %, and that the perforation rate was 11.1 %. He et al [13] reported that the complete resection rate of ESD for gastric SMTs was 100 %, and that the perforation rate was 19.35 %.However, another study conducted by Chun et al [14] demonstrated that the complete resection rate was only 74.3 %, and that the perforation rate was 6.1 %. In this study, the mean operation time was 115.1 min, which was relatively longer than that for previous reports [11,13,14].…”
mentioning
confidence: 99%
“…He et al [13] reported that the complete resection rate of ESD for gastric SMTs was 100 %, and that the perforation rate was 19.35 %.However, another study conducted by Chun et al [14] demonstrated that the complete resection rate was only 74.3 %, and that the perforation rate was 6.1 %. In this study, the mean operation time was 115.1 min, which was relatively longer than that for previous reports [11,13,14]. The possible explanations could be as follows: (i) some lesions had both intraluminal and extraluminal growth, which means that it would take more time to dissect tumors from the MP layer; (ii) twenty lesions were located in the gastric fundus, which means that more time would be consumed in the resection of tumors in the fundus compared with those in the body or the antrum.…”
mentioning
confidence: 99%